Impacto del libre flujo de capitales en la intermediación bancaria en el Perú: 1988-1997 - Coll Calderón, Lourdes (1998)
The inflow of capitals into Latin America during the 1990s attracted by more favorable economic indicators, such as a growing product and inflation under control, has allowed for the expansion in the volume of funds handled by the banking system, risking a deterioration of the quality of bank assets. This article examines the measures taken to control this problem in Peru, as well as in other countries in the region, in order to compare their results. We also make a review of the new bank supervision norms, and an analysis of the risk that has not yet been covered with the application of the Basel norms.